Recycling municipal solid waste incineration slag and fly ash as precursors in low-range alkaline cements - Maria de Lurdes Lopes (2020)
Application of municipal solid waste incineration (MSWI) products - fly ash (MSW-FA) and bottom ash (MSW-BA), is increasingly popular, mostly due to the need to reintroduce it in the industrial chain, but also because its technical performance is constantly enhanced by a growing research effort. This paper deals with the less popular application of these wastes without the addition of a more competent precursor. Several pastes based on MSW-FA, MSW-BA or MSW-FA+MSW-BA were prepared, using sodium silicate or sodium hydroxide. Their overall performance was then assessed through mechanical (uniaxial compressive strength - UCS and seismic wave velocity), environmental (leaching) and durability tests (freeze-thaw and wetting-drying). Cement stabilised MSW-BA pastes were also tested, for reference. Results showed that a preliminary mechanical activation, achieved by milling, is fundamental; the activation with silicate is more effective than with hydroxide, especially in the case of the MSW-BA pastes, when the UCS values are more than triplicated (3-10 MPa); the MSW-BA is a more competent precursor than the MSW-FA and the durability and leachability of the alkali activated pastes is similar to that obtained with cement. The most performing paste, in terms of UCS, was obtained with BA activated exclusively with sodium silicate, with an activator/precursor weight ratio of 0.5. In general, the low-cost solidification/stabilisation proposed in this study showed competitive with the alternative use of up to 30% cement and should be regarded as a valid alternative for simple storage or low-range applications, in substitution of Portland cement.